The making of a museum - Nasby, Judith, 1945- (Footprints series (Montréal, Quebec), 2021)
"Judith Nasby, founding director and curator of the Macdonald Stewart Art Centre, animates the story of the gallery from its humble beginnings in the hallways of a university campus in 1916 to its latest incarnation as the internationally recognized Art Gallery of Guelph. The book is beautifully illustrated with eighty images of artworks in the permanent collection, beginning with the gallery's first acquisition, Tom Thomson's 1917 masterpiece The Drive, the last large canvas he painted before his tragic death. As curator, Nasby oversaw the creation of one of the most comprehensive sculpture parks in Canada and the amassing of a permanent collection of some nine thousand artworks. In The Making of a Museum Nasby reveals how the museum developed its internationally recognized collection of contemporary Inuit drawings and wall hangings that toured four continents. She discusses the development of the collection's specializations in contemporary works by Canadian silversmiths; historical European etchings; Haudenosaunee beadwork; and others that arose from curatorial collaborations, such as molas by Kuna women artists from Panama and contemporary paintings and Indigenous woodcuts from Chongqing, China. Nasby recounts her long career as founding director and curator, peppering the hundred-year history of cultural development on the University of Guelph campus and in the city with humorous anecdotes and personal insights to reveal how arts institutions can be created through dedication, serendipity, and perseverance."--